Labor Law Regulations on Agile Work System from The Perspective Of Dignified Justice Theory - Joshua Irawan; Jenifer Wibisono Chietra; Leonardo Nathanael Morong; Vicariya Retnowati Boong; Sugeng Santoso Pudyo Nugroho (Journal of Law and Policy Transformation, 2025)
The Agile Work System allows employees to work flexibly in terms of time and location. This research focuses on flexible working hours as a key aspect of that system. Currently, Article 77 Paragraph (2) of Law 6/2023 and Article 23 of Government Regulation 35/2021 permit flexible hours only in certain sectors. However, many other sectors have already adopted flexible work practices, making these regulations outdated. Therefore, the laws should be revised to include all sectors and ensure fairness and protection for workers. This study uses a normative juridical approach, drawing on legislative analysis and the Theory of Dignified Justice. It aims to propose changes to existing regulations so they better accommodate flexible working arrangements. The authors recommend amending the current law to allow flexible working across all sectors, with clear requirements to protect workers’ rights.They also propose that flexible working arrangements must still comply with labor laws, including rules on overtime and wages. Additionally, the research suggests that both central and regional governments should supervise, review, and evaluate the implementation of agile work systems, focusing on continuous improvement and the protection of workers’ rights. In conclusion, the research supports a legal framework for agile work that is fair, inclusive, and respectful of workers’ dignity.